FAKTOR PENYEBAB KREDIT MACET DAN UPAYA PENANGGULANGAN DAN PENYELESAIANNYA DI BRI (STUDI KASUS BRI UNIT LEMABANG PALEMBANG) - Yun Suprani (JURNAL KOMPETITIF, 2013)
ABSTRACT Analysis of Factor Contributing to Credit loan and Mitigation Effects and the Solution to BRI Palembang using qualitative descriptive analysis technique. From the result of conducted can be found that the percentage of non performing loans in the BRI Unit Lemabang in 2008 is as high as 25,5% for loans amounting Kupedes, 0,38% for Fixed Income Group loans, and 27,47% for KUR loans due to bank extern factors.To deal with nonperformking loans arising PT Bank Rakyat Indonesia (BRI) Persero Tbk unit Lemabang trying to cope Palembang by analysing 5C, establish good relationship with consumers, monitoring the use of credit and billing. As well as using the model solution to saving through restructuring and setllement of credit through a peacefull setlllement by selling the collateral under the band. Key Words: Factor Contributing to Credit Loan, Mitigation Effects, Solution